Pemikiran Pendidikan Islam Perspektif KH. Hasyim Asy”Ari - Nur Amira; Tria Julita; Fany Rahmadiani; Erwin Syahwira; M. Rizki Alfattah; Rendy HandanI (PT PUSTAKA CENDEKIA GROUP, 2025)
This article examines Islamic educational thought from the perspective of KH. Hasyim Asy'ari, a great cleric and founder of Nahdatul Ulama (NU). His thoughts have significant relevance in the context of Islamic education in Indonesia. This study aims to analyze the philosophical foundations, objectives, curriculum, teaching methods, and teachers and students in the view of KH. Hasyim Asy'ari. Through literature studies and analysis of his works, this article shows that Islamic education according to KH. Hasyim Asy'ari is not only oriented towards cognitive aspects, but also emphasizes the formation of strong character, morals, and spirituality, as well as devotion to society and the state.